Local‐ and landscape‐scale impacts of clear‐cuts and climate change on surface water dissolved organic carbon in boreal forests. Issue 11 (25th November 2015) - Oni, Stephen K.; Tiwari, Tejshree; Ledesma, José L. J.; Ågren, Anneli M.; Teutschbein, Claudia; Schelker, Jakob; Laudon, Hjalmar; Futter, Martyn N.
Abstract: Forest harvesting and climate change may significantly increase concentrations and fluxes of dissolved organic carbon (DOC) in boreal surface waters. However, the likely magnitude of any effect will vary depending on the landscape‐element type and spatial scale. We used a chain of hydrological, empirical, and process‐based biogeochemical models coupled to an ensemble of downscaled Regional Climate Model experiments to develop scenario storylines for local‐ and landscape‐scale effects of forest harvesting and climate change on surface water DOC concentrations and fluxes. Local‐scale runoff, soil temperature, and DOC dynamics were simulated for a range of forest and wetland landscape‐element types and at the larger landscape scale. The results indicated that climate change will likely lead to greater winter flows and earlier, smaller spring peaks. Both forest harvesting and climate change scenarios resulted in large increases in summer and autumn runoff and higher DOC fluxes. Forest harvesting effects were clearly apparent at local scales. While at the landscape scale, approximately 1 mg L −1 (or 10%) of the DOC in surface waters can be attributed to clear‐cuts, both climate change and intensified forestry can each increase DOC concentrations by another 1 mg L −1 in the future, which is less than that seen in many waterbodies recovering from acidification. These effects of forestry and climate change on surface water DOC concentrations are additive at a landscape scale but not at the local scale, where a range of landscape‐element specific responses were observed. Key Points: Climate change and forestry will have a limited impact on boreal [DOC] Climate and forestry effects are not additive at a local scale Climate and forestry effects are additive at a landscape scale